Hot Links. (Communications of the ACM, 2004)
The article lists the most popular papers from ACM's referred journals and conference proceedings, the top courses and books at the ACM Professional Development Center and the top magazines and computing surveys articles for August 2004. The papers include "Lamport on Mutual Exclusion," by James H. Anderson, "Case Studies on Testing Object-Oriented Programs," by Roong-Ko Doong and Phyllis G. Frankl, "TCPA, Palladium and Friends," by William J. Caelli, "IPNL," by Paul Francis Ramakrishna, "Reasoning With Higher-Order Abstract Syntax in a Logical Framework," by Raymond C. McDowell and Dale A. Miller. The top courses and books include "Introduction to the Java Programming Language," "UML Fundamentals," "Data Modeling, Basic Programming in C," "Introduction to SQL, Part 1," "An Introduction to XML for Developers." The top magazines and computing surveys articles include "The Profession of IT: Who Are We?" by Peter J. Denning, "Aspect-Oriented Programming," by Tzilla Elrad, Robert E. Filman and Atef Bader, "Face Recognition," by W. Zhao, R. Chellappa, P.J. Phillips and A. Rosenfeld, "Data Clustering," by A.K. Jain, M.N. Murty and P.J. Flynn, and "Practical Programmer: On Personal Technical Obsolescence," by Robert L. Glass.